The Branding of the American Mind : How Universities Capture, Manage, and Monetize Intellectual Property and Why It Matters - Rooksby, Jacob H., 1982- (Book collections on Project MUSE., 2016)
Universities generate an enormous amount of intellectual property, including copyrights, trademarks, patents, Internet domain names, and even trade secrets. Until recently, universities often ceded ownership of this property to the faculty member or student who created or discovered it in the course of their research. Increasingly, though, universities have become protective of this property, claiming it for their own use and licensing it as a revenue source instead of allowing it to remain in the public sphere. Many universities now behave like private corporations, suing to protect trademarked sports logos, patents, and name brands. Yet how can private rights accumulation and enforcement further the public interest in higher education? What is to be gained and lost as institutions become more guarded and contentious in their orientation toward intellectual property? In this pioneering book, law professor Jacob H. Rooksby uses a mixture of qualitative, quantitative, and legal research methods to grapple with those central questions, exposing and critiquing the industry's unquestioned and growing embrace of intellectual property from the perspective of research in law, higher education, and the social sciences. While knowledge creation and dissemination have a long history in higher education, using intellectual property as a vehicle for rights staking and enforcement is a relatively new and, as Rooksby argues, dangerous phenomenon for the sector.